A specific aptamer-cell penetrating peptides complex delivered siRNA efficiently and suppressed prostate tumor growth in vivo. Issue 5 (3rd May 2016) - Diao, Yanjun; Liu, Jiayun; Ma, Yueyun; Su, Mingquan; Zhang, Hongyi; Hao, Xiaoke
ABSTRACT: Specific and efficient delivery of siRNA into intended tumor cells remains as a challenge, even though RNAi has been exploited as a new strategy for prostate cancer therapy. This work aims to address both specificity and efficiency of SURVIVIN -siRNA delivery by constructing a therapeutic complex using combinatorial strategies. A fusion protein STD was first expressed to serve as a backbone, consisting of streptavidin, a cell-penetrating peptide called Trans-Activator of Transcription (TAT) and a double-stranded RNA binding domain. A biotinylated Prostate Specific Membrane Antigen (PSMA) specific aptamer A10 and SURVIVIN- siRNA were then linked to STD protein to form the therapeutic complex. This complex could specifically targeted PSMA + tumor cells. Compared to lipofectamine and A10-siRNA chimera, it demonstrated higher efficiency in delivering siRNA into target cells by 19.2% and 59.9%, and increased apoptosis by 16.8% and 26.1% respectively. Upon systemic administration, this complex also showed significant efficacy in suppressing tumor growth in athymic mice ( p < 0.001 ). We conclude that this therapeutic complex could specifically and efficiently deliver SURVIVIN -siRNA to target cells and suppressed tumor growth in vivo, which indicates its potential to be used as a new strategy in prostate cancer therapy